Building structures illustrated : patterns, systems, and design - Ching, Frank, 1943- (John Wiley & Sons, Inc., 2014)
"Bestselling reference by reknowned authors of architectural design. One-stop guide to structural design in practice, meant for every designer's desktop. Illustrated throughout with Ching's trademark drawing. Treatment of structural design as part of the entire building design process. Includes overview of the historicial development of architectural materials and structures"--